Identity and Learning: a study on the effect of student-teacher gender matching on learning outcomes - Sukanta Bhattacharya; Aparajita Dasgupta; Kumarjit Mandal; Anirban Mukherjee (Global Labor Organization (GLO), 2020)
In this paper we examine whether students' and teachers' identity play any role in the learning outcome of students. Specifically, we ask if a student benefits by learning from a teacher of her same gender. Unlike the existing literature which explains such interaction through role model effect or Pygmalion effect, we explain such interaction in terms of gender based sorting behaviour across private and public schools. Our results are driven by two critical differences between male and female individuals. For male and female teachers, the difference comes from their differential transaction costs of traveling to schools at remote locations. For students, the difference between male and female members comes from the differential returns to education accrued to their parents; for girl students, a lower fraction of the return comes to their parental families as they start living with their husband's family after their marriages. These factors create a sorting pattern which makes the female teachers and students of the highest quality attend private schools in urban location. This creates a positive gender matching effect only for urban, private schools. We find support for our theoretical predictions when we test them using Young Lives Survey (YLS) data collected from Andhra Pradesh.
Keywords: I20; J16; 330; Teacher-student matching; Gender identity; Education; Gender norms; India